Situation with Fires and the Effectiveness of Fire Alarm Systems at Shipping Facilities - A. A. Poroshin; V. L. Zdor; N. V. Semenenko; I. V. Volkov (Безопасность техногенных и природных систем, 2022)
Introduction. Shipping, as one of the infrastructural transport communications, is a strategic branch of the economy of the Russian Federation. The timely delivery of goods, equipment, materials and raw materials to consumers depends on the reliability of shipping facilities operation. Therefore, ensuring safety, preventing man-made and natural destructive events are urgent and priority tasks of the owners of such facilities. Among the incidents that can cause significant direct and indirect damage, the most dangerous are fires. In this regard, in order to make management decisions on fire safety, it is necessary to know the situation with fires, to understand their social and economic consequences, to be able to identify possible causes for fires both at construction infrastructure facilities (shipyards, docks, port facilities) and on watercraft. At the same time, an important component in making such decisions is the study of the effectiveness of the fire alarm as a primary element in the general technological systems of fire automation on shipping facilities.Problem Statement. The objective of the study is to analyze the causes of fires and the operation of fire alarm systems at shipping facilities.Theoretical Part. Based on statistical data on fires and their consequences for 2017-2021, the social (the number of dead and injured people) and economic (direct material damage) consequences of fires at shipyards, port facilities, watercraft (ships, boats, vessels) and docks are analyzed. Estimates of the effectiveness of fire alarm systems at shipping facilities are given.Conclusions. The efficiency of fire alarm systems at all shipping facilities is on average at the level of 90%. At the same time, for sea and river vessels, this figure is about 82%, for port facilities it is almost 100%. But despite such a high level of fire alarm systems, it is not possible to avoid social and material consequences of fires. In addition, it should be noted that most fires occur at shipping facilities that are privately owned. At shipyards, port facilities and docks, fires on private property account for 71% of the total number of fires. On private sea and river vessels, the proportion of fires reaches 90%.